Academic System Design Of An-Nawari Madrasa In Sera Tengah Village With Simple Additive Weighting Method - Ach. Aden Ferdiyansyah; Johan Dharmawan (Journal of Public Policy Analys, 2024)
Abstract: Academic information systems are very useful in managing data and improving operational efficiency in educational institutions. Academic information systems speed up the administrative process and provide faster and easier access to information for those who need it. This research aims to design and build an Academic Information System (SIAKAD) at AN-NAWARI educational institutions in Sera Tengah village, especially at the Madrasah Tsanawiyah (MTs) level. In the process of designing this academic information system, a Decision Support System (SPK) is applied using the Simple Additive Weighting (SAW) method. The use of a decision support system aims to automatically rank students based on predetermined criteria. The data used in this study consisted of 46 MTS student data, divided into 16 seventh grade students, 14 eighth grade students, and 16 ninth grade MTS students. In addition, this study also uses 27 teacher data and odd semester value data for 2023–2024, for a total of 3,744 data points. The data collection methods used in this study include direct observation of the research location and interviews with related parties. The analysis technique used is mean absolute error (MAE), which aims to determine the level of error and the accuracy of the calculation results of the simple additive weighting method. The results of the data analysis show that the error rate is 12% and the accuracy rate is 88%. These results indicate that the research conducted was successful because it exceeded the target hypothesis that had been previously determined.